1998
DOI: 10.1095/biolreprod59.6.1328
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Removes Cholesterol from Mouse Sperm and Induces Capacitation in a Protein-Free Medium1

Abstract: Cyclodextrin, which stimulates cholesterol efflux from cells, was examined for its ability to induce capacitation of mouse spermatozoa. A chemically defined, protein-free medium was used for in vitro fertilization of cumulus-free mouse eggs. Fertilization did not occur in modified Krebs-Ringer bicarbonate medium (TYH) supplemented with 1 mg/ml polyvinylalcohol instead of BSA. However, fertilization was observed when spermatozoa were preincubated with methyl-beta-cyclodextrin (MBCD); fertilization rates increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 49 publications
11
101
2
1
Order By: Relevance
“…Cholesterol efflux induced in vitro by BSA or methyl-b-cyclodextrine (Choi & Toyoda 1998) and in vivo by progesterone (Costello et al 2009) and female tract neighborhood promotes the remodeling of the plasma membrane and triggers signaling pathways leading to different sperm processes that account for sperm fertilizing ability. Extracellular Ca 2C influx might induce Ca 2C /CaM-dependent NOS activity, increasing NO production.…”
Section: G S T -S P I N K 3 + S N P G S T -S P I N K 3 + G S N O G S mentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol efflux induced in vitro by BSA or methyl-b-cyclodextrine (Choi & Toyoda 1998) and in vivo by progesterone (Costello et al 2009) and female tract neighborhood promotes the remodeling of the plasma membrane and triggers signaling pathways leading to different sperm processes that account for sperm fertilizing ability. Extracellular Ca 2C influx might induce Ca 2C /CaM-dependent NOS activity, increasing NO production.…”
Section: G S T -S P I N K 3 + S N P G S T -S P I N K 3 + G S N O G S mentioning
confidence: 99%
“…Unless indicated, methyl-b-cyclodextrin was used as a replacement of 3% BSA for capacitation, since the latter may affect the fluorescence in the DAF-FM DA assay. The use of methyl-b-cyclodextrine has been already reported (Choi & Toyoda 1998). Sperm concentration was adjusted to the concentration indicated for each assay.…”
Section: Sperm Preparation and Capacitationmentioning
confidence: 99%
“…Non-physiological cholesterol acceptors such as cyclodextrins (cyclic oligosaccharides consisting of 7a (1-4)-glucopyranose units) have been shown to also alter the cholesterol content of sperm cell membranes (Ohtani et al 1989, Choi & Toyoda 1998, Flesch et al 2001 and induce an increase in PY (Osheroff et al 1999, Visconti et al 1999c. Interestingly, the cholesterol complexing agent, methyl-b-cyclodextrin (MbCD), does not require cholesterol oxidation in order to effectively remove cholesterol from the sperm plasma membrane (Boerke et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that methyl-β-cyclodextrin (MβCD) allows mouse spermatozoa to capacitate by promotion of cholesterol efflux from the plasma membrane [13][14][15]. Calcium ionophore A23187 is commonly used to induce the acrosome reaction in mammalian spermatozoa.…”
Section: Introductionmentioning
confidence: 99%